Pengaruh Sertifikat Bank Indonesia Syariah (SBIS), Jakarta Islamic Index (JII), Tingkat Inflasi, dan Index Harga Saham Gabungan (IHSG) Terhadap Nilai Tukar: Pendekatan Autoregressive Distributed LAG (ARDL) - Nur Fadhilah; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to review the effect of macro economic factors such as BankIndonesia Sharia Certificates (BISC), Jakarta Islamic Index (JII), Inflation, and Indonesia Composit Index (ICI) Against Exchange Rate of Rupiah Period 2013-2016 both long term and short term. This quantitative research used Autoregressive Distributed (ARDL) method. The data used is secondary data by collecting data from official website of Bank Indonesia, Yahoo Finance and PT. IDX) period 2013 to 2016. ARDL results show that In the short term variable JII, ICI, and BISC have a significant negative effect which means increaseing the variable will cause the Rupiah appreciate against the US Dollar. While variable Inflation has a positive value which means rising inflation will lead the Rupiah depreciate. In the Long run BISC and JII variable is negative and significant, while ICI is positive and inflation is negative not-significant.